Retiolitine graptolites from the Aeronian and lower Telychian (Llandovery, Silurian) of Arctic Canada. (21st November 2016) - Melchin, Michael J.; Lenz, Alfred C.; Kozłowska, Anna
Abstract: An exceptional fauna of retiolitine graptolites from Aeronian and lowermost Telychian strata in Arctic Canada provides significant new insights into the phylogeny and history of diversity of retiolitine graptolites. All specimens were isolated by dissolution of calcite concretions. The results indicate that retiolitines emerged within the lower Aeronian and reached a higher than expected level of diversity and disparity of forms by mid-Aeronian time. The uppermost Aeronian is almost totally devoid of preserved graptolites in Arctic Canada and, therefore, our material provides few new insights into retiolitine morphology or diversity through that interval. Specimens assigned to Pseudoretiolites ? sp. occur in well-dated lower Aeronian strata, thus representing the lowest known biostratigraphic occurrences of retiolitines globally. This taxon appears to be morphologically primitive in that the sicula is completely preserved, with preservation of the proximal regions of theca 1 1, as well as distal thecal fusellum on mature specimens. Cladistic analysis of the Llandovery retiolitines shows that Pseudoretiolites is a stem genus for all of the other retiolitine taxa, which comprise two clades: one consisting of Pseudoplegmatograptus, Retiolites, and Stomatograptus and their derivatives; and the other includes Rotaretiolites, Aeroretiolites, Aeroretiolites ?, Eorograptus, Paraplectograptus, Paraplectograptus ?, and Sokolovograptus, and all of those other taxa that had previously been placed in the Plectograptinae. We follow the recent proposal that all of the taxa traditionally assigned to the Retiolitidae be assigned to the subfamily Retiolitinae. The following new taxa are described: Pseudoretiolites hyrichus n. sp., Eorograptus spirifer n. sp., and Aeroretiolites cancellatus n. gen. n. sp.